2019
DOI: 10.1007/s11109-019-09560-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Attitudes and Independence Vote Choice

Abstract: In this article, we examine the impact of risk attitudes on vote choice in the context of a salient referendum with high levels of uncertainty about the consequences of the ballot proposal. Using data from a pre-and post-referendum panel survey conducted in the context of the 2014 independence referendum in Scotland, and a specific battery to measure attitudes to risk, we determine how these attitudes operate in such political contexts. We reach two main conclusions. First, risk attitudes have a direct effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 69 publications
1
21
0
1
Order By: Relevance
“…Justifying secession in such terms also makes strategic sense given that studies of referendum campaigns in Quebec and Scotland have suggested that pro-independence parties are usually confronted with risk-averse voters who tend to favour the constitutional status quo (Liñeira & Henderson, 2019;Nadeau et al, 1999) and political parties opposed to secession whose campaigns tend to focus on the risks and high costs of such a decision (Lecours, 2020;Mitchell, 2016). However, the Catalan case differs from these examples in a key respect: Whilst the UK and Canadian governments did not question the legitimacy of the referendum, the Spanish government has strongly contested the legality and constitutionality of such efforts (Balcells et al, 2020).…”
Section: Discussion: Explaining Catalan Secessionists' Justifications Of Independencementioning
confidence: 99%
“…Justifying secession in such terms also makes strategic sense given that studies of referendum campaigns in Quebec and Scotland have suggested that pro-independence parties are usually confronted with risk-averse voters who tend to favour the constitutional status quo (Liñeira & Henderson, 2019;Nadeau et al, 1999) and political parties opposed to secession whose campaigns tend to focus on the risks and high costs of such a decision (Lecours, 2020;Mitchell, 2016). However, the Catalan case differs from these examples in a key respect: Whilst the UK and Canadian governments did not question the legitimacy of the referendum, the Spanish government has strongly contested the legality and constitutionality of such efforts (Balcells et al, 2020).…”
Section: Discussion: Explaining Catalan Secessionists' Justifications Of Independencementioning
confidence: 99%
“…We account for respondents' age (logged), education (year finished primary education), gender and household income. 4 Young, male, low education and income respondents will be more supportive of Scottish independence (Park et al 2012;Liñeira and Henderson 2019). We present logistic regression estimates with robust standard errors.…”
Section: Methodsmentioning
confidence: 97%
“…In particular, more recently Eckles et al (2014) have shown empirically that citizens who are more risk averse are more likely to support incumbent candidates in US congress elections, while citizens who are more risk tolerant are more likely to vote for challengers. Similarly, Sanders and Jenkins (2016), Morisi (2018), Li ñeira and Henderson (2019) show that more risk-averse individuals are more likely to vote for the "status quo" policy in the recent UK "Leave" and Scotland "Independence" referenda, respectively.…”
Section: Physiological E Ectsmentioning
confidence: 96%